2014
DOI: 10.1177/0170840614556915
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotionally Important Social Identities on the Construction of a Managerial Leader Identity: A Challenge for Nurses in the English National Health Service

Abstract: The ability of individuals to accommodate emotional transition into roles requiring the construction of a leader identity is a poorly explored area. In this paper we consider the experience of 32 individuals moving into middle management positions, exploring how an emotional attachment to their professional group identity may cause identity conflict during the construction of a managerial leader identity. We consider how competing desired identities can result in negative emotional experiences, calling into qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 75 publications
(196 reference statements)
2
124
1
2
Order By: Relevance
“…Consistent with recent research on hybrid roles in healthcare (Croft et al 2015, Mc Givern et al, 2015, our DMs strongly identified with their clinical role. They all described themselves as doctors, typically saying, 'it doesn't matter what you do, above else you are a doctor!'…”
Section: Doctor Managers' Shared Professional Identity and Divergentsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with recent research on hybrid roles in healthcare (Croft et al 2015, Mc Givern et al, 2015, our DMs strongly identified with their clinical role. They all described themselves as doctors, typically saying, 'it doesn't matter what you do, above else you are a doctor!'…”
Section: Doctor Managers' Shared Professional Identity and Divergentsupporting
confidence: 91%
“…Our research integrates knowledge from psychology and organization studies in the 'generative dance' suggested by Currie et al (2012) and contributes to the burgeoning literature on identity work in healthcare professions, considered at a micro-level of practice (Currie et al 2010;Croft et al 2015;McGivern et al 2015).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations